Alcohol intake, beverage type, and lung function: a multicohort study of Chinese adults. Issue 1 (25th January 2022) - Wang, Dongming; Cao, Limin; Zhou, Min; Ma, Jixuan; Wang, Bin; Yuan, Jing; Chen, Weihong
Abstract: We aimed to investigate whether alcohol intake contributes to lung function levels and which beverage type may have an effect. We investigated 3742 participants from the Wuhai‐Zhuhai Cohort and 12, 526 participants from the Dongfeng‐Tongji Cohort, and they were followed up for 3 and 5 years, respectively. Information on the type and daily amount of alcohol intake was collected through face‐to‐face interviews. Lung function was measured by trained physicians using electronic spirometers. Compared with nondrinkers, moderate alcohol intake was significantly associated with a 70.03 and 74.92 mL increase in FEV1 and FVC, respectively ( P < 0.05), after adjusting for covariates. With regard to beverage type, red wine was associated with a 105.31 and 98.91 mL increase in FEV1 and FVC, respectively ( P < 0.05). Moderate alcohol intake was also associated with a 53.37 and 66.17 mL increase in FEV1 and FVC for liquor, respectively, and a 106.90 and 103.62 mL increase for red wine (all P s < 0.05). In the longitudinal analyses, moderate alcohol intake and red wine were associated with a 67.77 and 103.77 mL increase in FVC, respectively ( P < 0.05). Moderate alcohol intake is associated with increased lung function, especially for red wine. Further studies are needed to investigate the potential mechanism. Abstract : We explored the relationship between alcohol consumption and lung function in a large adult population from three cities in China. Alcohol consumption information, including average daily amount of alcohol intake and beverage type, were collected through face‐to‐face interviews, and a lung function test was conducted for each participant. We also investigated the associations between average daily amount of alcohol intake and lung function using different beverage types as a stratification variable.